2013
DOI: 10.1039/c3lc50672j
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide-linked gold nanoparticle aggregates for enhanced sensitivity in lateral flow assays

Abstract: Lateral flow assays (LFAs) as rapid analytical techniques promise to be widely used in point-of-care (POC) diagnostics because of their affordability and simplicity. However, LFAs still suffer from low sensitivity in detection of various biomarkers, e.g., nucleic acids. In this study, we developed a simple and general one-step signal amplification strategy, which employed oligonucleotide-linked gold nanoparticle (AuNP) aggregates to enhance the sensitivity in nucleic acid lateral flow (NALF) assays. Using a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(101 citation statements)
references
References 32 publications
1
99
0
1
Order By: Relevance
“…In our previous study, 23 the lateral flow test strip was constituted with NC membrane, absorbent pad and sample pad ( Figure 2A[i]). However, throughout our experiment on BNP detection, we found that the complex of GNP-Ab was unable to completely wick through the previously used sample pad, resulting in the waste and reduction of the effective tracer and degrade the detection sensitivity.…”
Section: Optimization Of Lfiasmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, 23 the lateral flow test strip was constituted with NC membrane, absorbent pad and sample pad ( Figure 2A[i]). However, throughout our experiment on BNP detection, we found that the complex of GNP-Ab was unable to completely wick through the previously used sample pad, resulting in the waste and reduction of the effective tracer and degrade the detection sensitivity.…”
Section: Optimization Of Lfiasmentioning
confidence: 99%
“…Therefore, BNP represents a vital blood cardiac biomarker in patients with acute myocardial infarction and advanced HF. 12 With advances in POC testing, [18][19][20][21][22] lateral flow assays (LFAs) hold tremendous potential to address the abovementioned challenges 23,24 due to the simple, affordable and user-friendly features. 25 However, the existing LFAs are associated with the limitation of poor sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, researchers have worked on different labeling tags, including silver or gold enhancement (Anfossi et al, 2013;Hu et al, 2013), chemiluminescent tags or fluorescent tags (Zou et al, 2010;Berlina et al, 2013;Bruno, 2014;Taranova et al, 2015), magnetic nanoparticles Wang et al, 2013), and carbon nanoparticles (Noguera et al, 2011). Anfossi et al (2013) amplified the detection signal of an ochratoxin by using a detection LFTS that utilizes silver nucleation on gold nanoparticles.…”
Section: Labeling Tagsmentioning
confidence: 99%
“…Among POCT devices, paper-based devices have been seen as the ideal platform for point-of-care (POC) diagnostics due to their very low cost, simplicity, and inherent ability to wick fluids. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Fluid transport eliminates expensive pumping instrumentation and complicated handling. 16,17 The porous structure of paper is very convenient for dot-immunobinding assays, and cellulose itself has high affinity to biomolecules.…”
Section: Introductionmentioning
confidence: 99%